Pengembangan Buku Pengayaan Menyajikan Gagasan dan Pendapat Teks Eksposisi Bermuatan Toleransi Beragama untuk Kelas VIII (widiyanto, 2022)
Tujuan dari penelitian ini adalah mendeskripsikan hasil analisis kebutuhan dan hasil pengembangan buku pengayaan menyajikan gagasan dan pendapat teks eksposisi bermuatan toleransi beragama untuk peserta didik kelas VIII. Penelitian ini menggunakan metode research and development (RD) dari Sugiyono (2017) yang dibatasi sampai lima langkah. Hasil analisis kebutuhan pengembangan menunjukkan bahwa peserta didik dan pendidik membutuhkan adanya pengembangan buku pengayaan menyajikan gagasan dan pendapat teks eksposisi bermuatan toleransi beragama. Hasil analisis tersebut dirumuskan menjadi prinsip-prinsip pengembangan untuk menyusun purwarupa buku pengayaan menyajikan gagasan dan pendapat teks eksposisi bermuatan toleransi beragama. Setelah purwarupa disusun, purwarupa diujikan kepada dua dosen ahli. Dari uji validasi tersebut, dinyatakan bahwa purwarupa buku pengayaan menyajikan gagasan dan pendapat teks eksposisi bermuatan toleransi beragama termasuk dalam kriteria buku pengayaan yang bagus, sehingga buku pengayaaan tersebut dapat digunakan sebagai penunjang buku teks yang diterbitkan pemerintah dalam meningkatkan kompetensi peserta didik SMP kelas VIII.The purpose of this study was to describe the results of the needs analysis and the results of the development of an enrichment book presenting ideas and opinions of an exposition text containing religious tolerance for grade VIII students. This study uses the research and development (RD) method from Sugiyono (2017) which is limited to five steps. The results of the needs analysis show that students and educators need the development of an enrichment book presenting ideas and opinions of exposition text with religious tolerance. The results of the analysis were formulated into development principles to compile an enrichment book prototype presenting ideas and opinions of an exposition text containing religious tolerance. After the prototypes were compiled, they were tested on two expert lecturers. From the validation test, it is stated that the enrichment book prototype presents ideas and opinions of exposition text containing religious tolerance which are included in the criteria for good enrichment books, so that these enrichment books can be used as supporting books for textbooks published by the government in improving the competence of VIII grade junior high school students.